Ethyl 2-(4-chloro-3-methylphenoxy)acetate - Yasser Hussein Issa Mohammed; S. Naveen; N. K. Lokanath; Shaukath Ara Khanum (IUCrData, 2016)
In the title compound, C11H13ClO3, the pendant ethyl chain has an extended conformation and lies in the plane of the substituted benzene ring; the r.m.s. deviation of the 15 non-H atoms comprising the molecule is 0.002 Å. The crystal structure features inversion-related dimers linked by pairs of benzene–carbonyl C—H...O hydrogen bonds, generating R22(16) loops.